The mandible of Compsodon helmoedi (Therapsida: Anomodontia), with new records from the Ruhuhu Basin, Tanzania - Angielczyk, Kenneth D.; Peecook, Brandon R.; Smith, Roger M. H. (My University, 2023)
The emydopoid dicynodont Compsodon helmoedi originally was named from a single skull collected in Daptocephalus Assemblage Zone strata in the South African Karoo Basin. Recently described specimens from the Luangwa Basin, Zambia, have elucidated the species’ cranial morphology and facilitated identification of other historical Karoo specimens. Neither the holotype nor any of the described Zambian specimens preserve a mandible; a referred Karoo specimen preserves a highly damaged mandible, but poor preservation obscures most details.We present an additional Zambian Compsodon specimen that includes an articulated cranium and mandible, and use μCT data to describe the mandible of this taxon for the first time. The mandible has an upturned dentary symphysis; ‘postcanine’ teeth with coarse distal denticles; a shallow, elongate posterior dentary sulcus with medial expansion anterior to the tooth row, and a prominent lateral dentary shelf. Although the mandible is similar to those of Emydops and Pristerodon, it can be differentiated from Emydops by the latter’s more triangular posterior dentary sulcus, and the absence of a rugose muscle scar on the lateral edge of the lateral dentary shelf. It differs from Pristerodon in the absence of a dentary table rostral to the tooth row, the presence of a transverse ridge dividing the lateral dentary shelf into posterior and anterior sections, and the anterodorsal angulation of the lateral dentary shelf. Three fragmentary specimens from the Usili Formation (Ruhuhu Basin) display the same morphotype and represent the first record of Compsodon from Tanzania. The expanding geographic range of Compsodon underscores its potential as a biostratigraphic index fossil, but more information on its stratigraphic and temporal ranges is needed to realize that potential.